Leadership Support for School Principals: Strategies for the Implementation of the Kurikulum Merdeka - Suarka, Suarka; Harapan, Edi; Rosani, Meilia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The formulation of this thesis problem is how to obtain the Assistance of the Principal in implementing the Kurikulum Merdeka at 154 Palembang State Elementary School. The results of the study show that the Assistance carried out by the Principal in implementing the Kurikulum Merdeka at the 154 Palembang State Elementary School, has been carried out well. However, it is only in the early stages, namely in the stage of the Independent Learning pathway, in other words, that the educational unit has applied several principles of the Kurikulum Merdeka in the implementation of learning and assessment but still uses the curriculum of the academic unit that is currently implemented, namely Curriculum 13. Thus, the Principal's Assistance in implementing the Kurikulum Merdeka at 154 Palembang State Elementary School has been implemented. However, the implementation has yet to be fully implemented on the Independent Change and Sharing pathway.